FEATURES OF CULTURAL AND LEISURE ACTIVITIES OF REPRESENTATIVES OF THE YOUNGER GENERATION - Kirill B. Safonov (Russian Studies in Culture and Society)
The article is devoted to the study of the features of cultural and leisure activities of modern youth. The author notes that properly organized leisure plays an important role in the personal development of every young person. The result of this can be considered the optimization of the processes of socialization and social adaptation of the younger generation.